LEGAL TRADITION AND LEGAL CULTURE IN THE SYSTEM OF NATIONAL PATRIOTIC EDUCATION OF YOUTH - Shevchuk Mykhailo (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького, 2023)
Purpose. The purpose of our research is to determine the content of the concepts of legal tradition and legal culture, as well as to establish their role in the process of national-patriotic education of young people. Method. The methodological basis of scientific research was a system of general scientific, special scientific and philosophical methods, as well as principles and methods of scientific knowledge. Results. It was established that «legal tradition» and «legal culture» are concepts of different content levels. «Legal tradition» is a more general and systemic concept, because it allows us to understand the way and reasons for the formation of the legal system, its evolution in historical being, the peculiarities of the implementation of legal norms, etc. Instead, «legal culture» reflects the level of development of the legal system at a specific stage of its development. It can be argued that «legal culture» forms «legal tradition». From the level of development of «legal tradition» and «legal culture» we can talk about the level of legal awareness of the country's population, about its legal activity and even legal memory. It is important that in today's conditions, when the influence of the information space is growing, globalization challenges are intensifying, various forms of hybrid conflicts are being implemented, national-patriotic education should be carried out exclusively at the level of transformation of legal culture and legal tradition. Scientific novelty. The thesis that the concepts of «legal tradition» and «legal culture» are important categories of legal understanding and express the way of formation of the legal system of a specific state is substantiated. At the same time, we consider the concept of «legal tradition» to be broader and such that it not only reveals historical experience in the process of formation and use of law by individual peoples, but also indicates the vector of development of society, reflects the level of its perception of law. Regarding the concept of «legal culture», it is narrower and primarily reflects legal perception in specific time frames. Both of these concepts are important in the context of implementing national-patriotic education. Practical significance. The achieved results can be used in the process of further theoretical and legal research, preparation of individual special courses.